PREDIKSI PENYAKIT DIABETES MENGGUNAKAN ALGORITMA REGRESI LOGISTIK - Sugianto; Andi Maslan (Computer Science and Industrial Engineering, 2024)
The annual count of individuals afflicted with diabetes is rising. As to a survey carried out by the International Diabetes Federation (IDF), the global diabetes population is approximated to be 537 million by 2021, and this number is projected to increase further to exceed 780 million by 2045. The study's primary goal is to diagnose and forecast whether or not a patient has diabetes. The approach makes use of logistic regression, a statistical tool for modelling individual classifications of diabetes presence or absence. According to the diabetes risk prediction results, 43% of respondents gave consideration to the condition. Consequently, it has been demonstrated that normalisation enhances the accuracy of diabetes risk prediction using logistic regression methods. Based on the variables included, it is anticipated that the predictions made by this model will serve as a guide for the general public in understanding healthy living and diabetes prevention.